Impacts of Pangasius aquaculture on land use patterns in Mymensingh district of Bangladesh - Ali, H; Haque, MM (Journal of the Bangladesh Agricultural University, 2011)
Pangasius catfish, Pangasianodoan hypophthalmus farming has been evolved to a shape of commercial enterprise over the last two decades in north-central part of Bangladesh, particularly in Mymensingh area but there is a lack of quantitative and qualitative data on the impacts of it on land use pattern. This study was conducted using multiple methodological tools including participatory rural appraisal (PRA) tools and mainly questionnaire based farm survey to assess the impacts of Pangasius farming on land use from February to September, 2009. The mean farm size (ha), water area (ha) and dyke area (ha) was 1.36±1.25, 1.06±1.31 and 0.30±0.27, respectively. The Pangasius productivity was significantly and positively correlated with water area and dyke area. Around 10.1% area of the study area was converted to Pangasius farm which was previously used as rice-field. Farmers expanded their farm area by taking leased lands which contributed to 56.47% of total farm area and the lease value of Pangasius pond was doubled compared to agriculture land. Around 48% area of dyke were used to produce agriculture crops and the production was 71.01% lower but profit margin was 76.58% higher than normal land. The discharging wastewater of Pangasius pond also increased rice productivity in adjacent agriculture farm by 10% and additionally reduced fertilizer and irrigation cost by 30% and 40%, respectively. Keyword: Pangasius aquaculture; impact on land use pattern; Bangladesh DOI: http://dx.doi.org/10.3329/jbau.v9i1.8759 JBAU 2011; 9(1): 169-178